1997
DOI: 10.1126/science.278.5342.1447
|View full text |Cite
|
Sign up to set email alerts
|

Vigorous HIV-1-Specific CD4 + T Cell Responses Associated with Control of Viremia

Abstract: Virus-specific CD4+ T helper lymphocytes are critical to the maintenance of effective immunity in a number of chronic viral infections, but are characteristically undetectable in chronic human immunodeficiency virus-type 1 (HIV-1) infection. In individuals who control viremia in the absence of antiviral therapy, polyclonal, persistent, and vigorous HIV-1-specific CD4+ T cell proliferative responses were present, resulting in the elaboration of interferon-gamma and antiviral beta chemokines. In persons with chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

64
1,212
12
15

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,738 publications
(1,308 citation statements)
references
References 33 publications
64
1,212
12
15
Order By: Relevance
“…The model is based on previous work which investigated virus spread via the mitotic division of T cells [9,10] and is given by the following set of differential equations. (2) The dynamics may converge to two different stable equilibria. (i) The CD4 T cell response, and thus virus replication in specific T cells, does not become established.…”
Section: Infectious and Autocatalytic Virus Spread In T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The model is based on previous work which investigated virus spread via the mitotic division of T cells [9,10] and is given by the following set of differential equations. (2) The dynamics may converge to two different stable equilibria. (i) The CD4 T cell response, and thus virus replication in specific T cells, does not become established.…”
Section: Infectious and Autocatalytic Virus Spread In T Cellsmentioning
confidence: 99%
“…(The higher the virus load, the more efficient the rate of mitotic spread). Infection of HIV-specific CD4 T cells can also result in efficient impairment of effector responses, such as cytotoxic T lymphocytes (CTL) or antibodies, because the ability to deliver help may be subverted [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…This may be extrapolated to other viruses causing persistent infections, in particular HIV. For HIV, it has been shown that long-term control of viral replication is tightly associated with the maintenance of a functional Th cell response [43][44][45]. Moreover, induction of HIV-specific neutralizing antibodies shows kinetics that are comparable to those observed after LCMV infection [46].…”
Section: Resultsmentioning
confidence: 98%
“…113 On the contrary, control of viremia was associated with a polyclonal, vigorous HIVspecific CD4 þ T-cell response accompanied by a strong CTL response. 114 As mentioned, reconstitution of CD28 expression in CD28 HIV-specific CD8 þ T cells results in the restoration of autocrine production of IL-2 and antigen-specific proliferation, suggesting an increased dependence on CD4 þ T-cell help in the absence of CD28 and impaired ability for IL-2 production. 105 Furthermore, diminished IL-2 could further deteriorate the CTL response through the downregulation of proliferation of HIV-specific CD4 þ T cells.…”
Section: Loss Of Hiv-specific Cd4 þ T-cell Helpmentioning
confidence: 86%